Association of serum vitamin D levels and urinary tract infection in pregnant women: A case control study. (December 2019) - Haghdoost, Simin; Pazandeh, Farzaneh; Darvish, Soodabeh; Khabazkhoob, Mehdi; Huss, Reinhard; Lak, Tahereh Behroozi
Abstract: Objective: Urinary tract infection (UTI) is common during pregnancy and can cause serious complications for the mother and fetus. Vitamin D, is known to have an effect on the urothelium, with immunomodulatory capacity against bacterial infection. This study explored the association between serum vitamin D levels and urinary tract infections in pregnant women. Study design: In this case control study, 187 participants including, 97 pregnant women diagnosed as a symptomatic UTI (case group) and 90 matched healthy pregnant women (control group) were consecutively enrolled from prenatal care clinic of Imam Reza Hospital in Urmia, North West of Iran. The two groups were matched for trimester and parity, and sexual intercourse. Blood samples were collected from both groups. Chemiluminescent immunoassay (CLIA) was used to evaluate the serum vitamin D levels. We used a binary multivariate unconditional logistic regression approach to evaluate the association between UTI and vitamin D and risk factor of the UTI. Results: Vitamin D deficiency (less than 20 ng/mL) was diagnosed in 85.7% of case group and 52.2% of control group. The serum vitamin D levels were significantly lower in pregnant women in the case group compared to the control group (12.7 ± 5.9 ng/ml vs 26.05 ± 10.37; p < 0.001). Pregnant women in case group with acute pyelonephritis had significantly lower serum vitamin D levels than those with Cystitis (p < 0.05). The serum vitamin D level of less than 20 ng/ml was the only factor associated with UTI after adjusting for all the confounders in multiple binary logistic regression modeling (AdjOR = 3.67; 95% of CI: 1.19–6.24; p < 0.001). Conclusions: Women with vitamin D deficiencies are at increased risk of urinary tract infections during pregnancy. However, further studies are essential to confirm these observed results.